Women’s Health Decision-Making Autonomy and Skilled Birth Attendance in Ghana - Ameyaw, Edward Kwabena; Tanle, Augustine; Kissah-Korsah, Kwaku; Amo-Adjei, Joshua (International Journal of Reproductive Medicine, 2016)
Delivering in health facility under the supervision of skilled birth attendant is an important way of mitigating impacts of delivery complications. Empirical evidence suggests that decision-making autonomy is aligned with holistic wellbeing especially in the aspect of maternal and child health. The objective of this paper was to examine the relationship between women’s health decision-making autonomy and place of delivery in Ghana. We extracted data from the 2014 Ghana Demographic and Health Survey. Descriptive and logistic regression techniques were applied. The results indicated that women with health decision-making autonomy have higher tendency of health facility delivery as compared to those who are not autonomous [OR = 1.27, CI = 1.09–1.48]. However, those who have final say on household large purchases [OR = 0.71, CI = 0.59–0.84] and those having final say on visits [OR = 0.86, CI = 0.73–1.01] were less probable to deliver in health facility than those without such decision-making autonomy. Consistent with existing evidence, wealthier, urban, and highly educated women had higher inclination of health facility delivery. This study has stressed the need for interventions aimed at enhancing health facility delivery to target women without health decision-making autonomy and women with low education and wealth status, as this can play essential role in enhancing health facility delivery.